ESG Integration in the Light of Regression Analysis - P. I. Sevostyanov; Z. V. Bogaturiya (Вестник Российского экономического университета имени Г. В. Плеханова)
Ecological, social and corporate governance (ESG) becomes an important element in strategy of companies aiming at sustainable development. However, the process of ESG initiatives face serious challenges, including the absence of uniform accounting standards, expensive ESG strategy realization and shortage of reliable information. The goal of the present article is to study these problems and their impact on corporate governance. Using data of international consulting companies, such as McKinsey, MSCI, Sustainalytics, Bloomberg the authors analyzed problems dealing with ESG strategy realization and arising risks. The key component of the research is a mathematic model of multiple linear regression, which evaluates the quantitative impact of ESG factors on market company capitalization. The results of the analysis are demonstrated, they show the impact of ESG factors on company capitalization and it can explain the vector of their advance into corporate strategies. Provided conclusions have practical importance for business, researchers and regulating bodies wishing to improve integration of ESG practices in conditions of global economic turbulence. The novelty of the research includes the use of regression coefficient to evaluate ESG factors of market capitalization. These findings underline the necessity of well-balanced investment, data transparency and standard unification for successful ESG integration into corporate governance.